Anti-knife-sticking lithium battery high-temperature-resistant adhesive tape as well as preparation method and application thereof

By using materials such as polyethylene terephthalate and polyethylene resin, and using specific preparation methods, the existing tape has been solved inadequate performance stability, poor anti-adhesion effect, and insufficient mechanical strength and adhesion under high temperature environments, and a more efficient and safe lithium battery manufacturing is achieved.

CN119592244APending Publication Date: 2025-03-11FOSHAN SHUNDE YONGCHUANG XIANGYI ELECTRONIC MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411942852.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing anti-adhesive knife lithium battery high-temperature resistant tape has insufficient performance stability in high-temperature environments, poor anti-adhesive effect, insufficient mechanical strength and adhesion, which affects the manufacturing quality and safety of lithium battery.

Method used

Polyethylene terephthalate and polyethylene resin are used as substrates, combined with antioxidant 1076, phosphite and calcium stearate, and tape is prepared by drying, mixing, extrusion molding, bidirectional stretching, cooling, corona treatment and coating of adhesives.

Benefits of technology

It improves the thermal stability, anti-stick effect, mechanical strength and adhesion of the tape, and is suitable for lithium battery manufacturing, improving the efficiency and safety of the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of adhesive tapes, and discloses an anti-knife-sticking lithium battery high-temperature-resistant adhesive tape as well as a preparation method and application thereof. The adhesive tape comprises a base material and an adhesive layer, wherein the base material comprises the following components: polyethylene glycol terephthalate resin, polyethylene resin, an antioxidant 1076, phosphite ester and calcium stearate. Acrylic glue is selected as an adhesive of the adhesive layer of the adhesive tape. The preparation method comprises the steps of (1) drying, (2) mixing, (3) extrusion molding, (4) two-way stretching, (5) cooling, (6) corona treatment and (7) tackiness agent.The adhesive tape has the advantages of being high in heat stability, good in knife sticking prevention effect and high in mechanical strength and adhesiveness and is suitable for being used as the lithium battery adhesive tape.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesive tapes, and in particular to an anti-sticking high-temperature resistant adhesive tape for lithium batteries, and a preparation method and application thereof. Background Art

[0002] Lithium battery tape is a kind of tape specially used for lithium battery manufacturing and maintenance. It has multiple functions such as insulation, fixing, protection and sealing. This tape must be able to withstand the thermal expansion and mechanical stress generated by lithium batteries during charging and discharging. At the same time, it must also have high temperature resistance, electrolyte corrosion resistance, good bonding strength and certain mechanical strength. Lithium battery tape plays a vital role in the safety and performance of batteries, especially in electric vehicles and portable electronic devices.

[0003] In recent years, with the continuous development of lithium battery technology, the requirements for lithium battery tapes have become higher and higher. Especially in terms of preventing knife sticking and high temperature resistance, traditional tapes can no longer meet the needs of modern lithium battery manufacturing. Therefore, anti-stick knife lithium battery high temperature resistant tape came into being. This tape can not only effectively prevent knife sticking during cutting, coating and other processes, but also maintain stable performance under high temperature environment. At present, some anti-stick knife lithium battery high temperature resistant tapes have appeared on the market. They usually use polyimide film, polyamide film or composite film as the base material, and silicone adhesive or acrylate adhesive as the adhesive. The performance of these tapes can adapt to the thermal expansion and mechanical stress of lithium batteries during the charging and discharging process, and to a certain extent improve the efficiency and safety of lithium battery manufacturing process.

[0004] However, although the existing anti-sticking knife lithium battery high temperature resistant tape has made certain progress, there are still some problems. First, the performance stability of some tapes in high temperature environments is insufficient, and they are prone to deformation or decreased viscosity, which affects the manufacturing quality and safety of lithium batteries. Secondly, some tapes do not perform well in terms of anti-sticking properties, especially after long-term use or in high temperature environments, sticking to the knife will still occur, resulting in a decrease in the quality of tape cutting. In addition, some tapes are also insufficient in mechanical strength and adhesion, and cannot withstand various stresses and impacts in the manufacturing process of lithium batteries. The above problems limit the application and promotion of the existing anti-sticking knife lithium battery high temperature resistant tape in the field of lithium battery manufacturing. Therefore, it is urgent to propose an anti-sticking knife lithium battery high temperature resistant tape to solve the problems of insufficient thermal stability, poor anti-sticking effect, and insufficient mechanical strength and adhesion in the prior art. Summary of the invention

[0005] In view of the above defects or improvement needs of the prior art, the present invention provides an anti-sticking knife lithium battery high temperature resistant tape and its preparation method and application. The anti-sticking knife lithium battery high temperature resistant tape has the characteristics of strong thermal stability, good anti-sticking effect, strong mechanical strength and adhesion.

[0006] The purpose of the first aspect of the present invention is to provide a high temperature resistant tape for anti-sticking lithium batteries.

[0007] The purpose of the second aspect of the present invention is to provide a method for preparing the anti-sticking knife lithium battery high temperature resistant tape of the first aspect of the present invention.

[0008] The purpose of the third aspect of the present invention is to provide an application of the anti-sticking knife lithium battery high temperature resistant tape of the first aspect of the present invention.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is: A first aspect of the present invention provides an anti-sticking high temperature resistant tape for lithium batteries, the tape comprising a substrate and an adhesive layer.

[0010] Preferably, the substrate comprises the following components, each component being measured by weight: polyethylene terephthalate (PET) resin: 75-87 parts, polyethylene resin: 9-15 parts, antioxidant 1076: 1-4 parts, phosphite: 2-3 parts, and calcium stearate: 1-3 parts.

[0011] Preferably, the adhesive of the adhesive layer is acrylic glue.

[0012] More preferably, the substrate has a thickness of 20-25 μm.

[0013] More preferably, the adhesive layer has a thickness of 10-25 μm.

[0014] The second aspect of the present invention provides a method for preparing the anti-sticking knife lithium battery high temperature resistant tape of the first aspect of the present invention, comprising the following steps: 1) drying; 2) mixing; 3) extrusion molding; 4) biaxial stretching; 5) cooling; 6) corona treatment; 7) coating of adhesive.

[0015] Preferably, the step 1) drying comprises: drying the polyethylene terephthalate resin and the polyethylene resin in a drying oven at 130-150° C. for 3-5 hours to reduce the moisture content of the resin to less than 0.03%; Preferably, the step 2) mixing comprises: mixing the dried resin with antioxidant 1076, phosphite and calcium stearate in a high-speed mixer. The mixer speed is set to 600-1000 rpm and the mixing time is 10-15 minutes; Preferably, the step 3) extrusion molding includes: using a twin-screw extruder, adding the mixed raw materials into the extruder hopper, under the rotation of the screw, the raw materials are gradually plasticized and conveyed forward, and extruded through the slit die of the die head to form a thick sheet. The screw speed is set at 20-50 rpm according to the specifications and output requirements of the extruder; Preferably, the step 4) biaxial stretching comprises: firstly stretching the extruded thick film longitudinally. The stretching temperature is controlled at 85-95°C, the stretching ratio is 3-4 times, and the tension range is 8-12N / cm; the longitudinally stretched film is then stretched transversely. The preheating temperature is 100-110°C, the stretching temperature is 110-120°C, and the stretching ratio is 3.5-4.5 times. The stretched film is heat-set in the setting area at a temperature of 200-220°C for 5-10 seconds; Preferably, the step 5) cooling comprises: cooling by a cooling roller, wherein the temperature of the cooling roller is controlled at 20-30° C., so that the film is quickly cooled and shaped; Preferably, the step 6) corona treatment comprises: performing corona treatment by a corona treatment machine with a power of 2-5 kW and a treatment time of 1-3 seconds; Preferably, the step 7) coating the adhesive comprises: coating the adhesive on the surface of the substrate prepared in step 6, and drying.

[0016] A third aspect of the present invention provides an application of an anti-sticking high temperature resistant tape for lithium batteries, wherein the tape is applied in a lithium battery production process.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides an anti-sticking high temperature resistant tape for lithium batteries and a preparation method and application thereof. The present invention selects polyethylene terephthalate and polyethylene resin together as the substrate of the lithium battery tape, which has the advantages of good mechanical properties, excellent electrical properties, chemical stability and processing performance, which are not possessed by other substrates. In the production and application of lithium batteries, selecting a suitable tape substrate is crucial to improving the performance and safety of the battery. The present invention selects antioxidant 1076 as an antioxidant and selects phosphite as a thermal stabilizer. Compared with other antioxidants and thermal stabilizers, antioxidant 1076 and phosphite have good material compatibility with lithium battery tape, can be evenly dispersed in the tape material, are more easily combined with the tape material, and will not have stratification or precipitation, thereby exerting the best anti-oxidation and thermal stabilization effect. The present invention selects calcium stearate as a lubricant, which has the advantages of good thermal stability, strong compatibility, good anti-sticking property, low cost and good environmental protection, and plays an important role in improving processing performance, improving surface quality and preventing adhesion in the preparation of lithium battery tape. The adhesive tape of the invention has the characteristics of strong thermal stability, good anti-sticking knife effect, strong mechanical strength and adhesion, and is suitable for use as a lithium battery adhesive tape.

[0018] The present invention provides a method for preparing an anti-sticking high temperature resistant tape for lithium batteries, which is obtained by drying, mixing, extrusion molding, biaxial stretching, cooling and corona treatment, and finally coating an adhesive. Biaxial stretching treatment can enhance tensile strength, improve puncture resistance and improve insulation performance, thereby improving the mechanical properties of the tape and optimizing electrical properties. Corona treatment can increase the viscosity of the tape, ensure that the tape can function stably under various environmental conditions, and enhance stability. The preparation method provided by the present invention effectively solves the problems of insufficient thermal stability, poor anti-sticking effect, and insufficient mechanical strength and adhesion of the tape in the prior art, and promotes the application and promotion of anti-sticking high temperature resistant tape for lithium batteries in the field of lithium battery manufacturing.

[0019] The invention provides an application of an anti-sticking high temperature resistant adhesive tape for lithium batteries, which can be applied to the production process of lithium batteries and improves the efficiency and safety of the production process of lithium batteries to a certain extent. DETAILED DESCRIPTION

[0020] Now, in conjunction with specific embodiments, a high temperature resistant tape for lithium batteries and a preparation method and application thereof provided by the present invention are further described in detail, but the scope of the present invention is not limited thereto.

[0021] Unless otherwise specified, the materials used in this example were obtained from commercial sources.

[0022] On the one hand, the present invention provides an anti-sticking lithium battery high temperature resistant tape, which is composed of a base material and an adhesive layer.

[0023] The substrate comprises the following components, each component being calculated by weight: 75-87 parts of polyethylene terephthalate (PET) resin, 9-15 parts of polyethylene resin, 1-4 parts of antioxidant 1076, 2-3 parts of phosphite, and 1-3 parts of calcium stearate.

[0024] The substrate has a thickness of 20-25 μm.

[0025] The adhesive of the adhesive layer is acrylic glue with a thickness of 10-25 μm.

[0026] Furthermore, the base material formula is as follows: in parts by weight, polyethylene terephthalate resin (PET) 75-87 parts, polyethylene resin (PE) 9-15 parts, antioxidant 1076 1-4 parts, phosphite 2-3 parts, and calcium stearate 1-3 parts.

[0027] Furthermore, the polyethylene terephthalate resin (PET) is a thermoplastic resin, a member of the polyester family, and is prepared by polymerization of terephthalic acid (TPA) and ethylene glycol (EG). Polyethylene terephthalate resin is often used as a tape substrate due to its excellent physical and chemical properties. First, it has excellent mechanical properties. Polyethylene terephthalate resin has high tensile strength, rigidity and bending strength, so that the tape can withstand certain external forces during use without being easily deformed or damaged; at the same time, it also has good wear resistance and tear resistance, and can maintain a good appearance and performance during long-term use. It is not easy to tear and can remain intact even when subjected to large external forces, thereby extending the service life of the tape. Second, it has excellent chemical stability, has good tolerance to most chemical substances such as solvents, acids, alkalis, and oils, and has good oxidation resistance. It is not easy to oxidize and cause performance degradation or damage when exposed to air for a long time. Third, it has excellent thermal stability. Polyethylene terephthalate resin can maintain its physical and chemical properties in a wide temperature range, and the maximum operating temperature can reach 150°C. Therefore, the tape prepared from it can still maintain good performance in high temperature environments, has good dimensional stability, and is not prone to deformation, softening or loss of viscosity. It can be widely used in high-temperature working scenes; the thermal expansion coefficient is low, and temperature changes have little effect on its size. Fourth, it has excellent optical properties. The polyethylene terephthalate resin substrate has high transparency and is suitable for transparent tape without affecting the line of sight; the surface is smooth, has good gloss, and has a beautiful appearance. Fifth, it has excellent processing performance. Polyethylene terephthalate resin is easy to form and can be processed through a variety of processes such as blow molding, injection molding, and extrusion to make tape substrates of different thicknesses and shapes; printability. The surface of the polyethylene terephthalate resin substrate is easy to print, which is suitable for making tapes with logos or patterns. Sixth, it is environmentally friendly and recyclable. Polyethylene terephthalate resin is a recyclable material that helps reduce environmental pollution. Polyethylene terephthalate resin has low volatility during production and use and is environmentally friendly. Seventh, it is cost-effective. Compared with some high-performance special materials, the production cost of polyethylene terephthalate resin is relatively low, and the supply is sufficient. It can provide economic feasibility for large-scale production and wide application while ensuring certain performance, and has a high cost-effectiveness. Moreover, the tape prepared by it is durable and has a long service life, reducing the need for frequent replacement.

[0028] Furthermore, the polyethylene resin (PE) is a linear or branched high molecular polymer formed by polymerization of ethylene monomers. It has the following advantages when used as a tape substrate: First, it has excellent low temperature resistance. Polyethylene has excellent low temperature resistance. Its minimum operating temperature can reach -100°C to -70°C. It can still maintain good flexibility and mechanical properties in low temperature environments. It is not easy to become brittle or crack. Therefore, it is suitable for bonding and protection needs in various low temperature scenarios, such as frozen food packaging, sealing and fixing of low temperature equipment, etc. Second, it has good chemical stability, can withstand the erosion of most acids and alkalis, is insoluble in general solvents at room temperature, has low water absorption, has good stability in different chemical environments, is not prone to chemical reactions that lead to performance degradation or damage, and can be used in the presence of a variety of chemical substances. Third, it has strong electrical insulation properties and can be used as an electrical insulation material. It can effectively prevent current leakage, short circuits and other problems, and ensure the normal operation and safe use of electrical equipment. Fourth, it has good flexibility and elasticity, which enables the tape to adapt to objects of different shapes and surfaces, fit closely to the adhered object, provide a good sealing effect, and can deform to a certain extent after being subjected to external force without breaking easily, which enhances the applicability and durability of the tape.

[0029] Furthermore, the antioxidant 1076, whose chemical name is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester, is a highly efficient hindered phenol antioxidant with good thermal stability and antioxidant properties, and can effectively inhibit the oxidative degradation of polymer materials during processing and use. The main mechanism of action of antioxidant 1076 is to capture free radicals and interrupt the oxidation chain reaction, thereby protecting the polymer material from oxidative damage. Antioxidant 1076 has the following advantages when used as a raw material for preparing tape: First, it improves the antioxidant properties of the tape. During use, the tape may be affected by oxygen, heat, ultraviolet rays and other factors and undergo oxidative aging. The addition of antioxidant 1076 can effectively capture free radicals, decompose peroxides, delay the oxidation process of the tape, and increase the service life of the tape. Second, it enhances the thermal stability of the tape. Antioxidant 1076 itself has good thermal stability. As a raw material for preparing tape, it can improve the stability of the tape in a high temperature environment, making it less prone to deformation, softening and other problems. The third is to improve the physical properties of the tape. Antioxidant 1076 has good compatibility with other ingredients in the tape and can improve the physical properties of the tape, such as tensile strength, elongation at break, etc.; by optimizing the formula of the tape and making antioxidant 1076 work synergistically with other raw materials, the overall performance of the tape can be improved to meet the needs of different application scenarios.

[0030] Furthermore, the phosphite is a class of ester compounds, the basic structure of which is a compound containing a phosphorus oxygen bond and a phosphorus carbon bond, and is formed by replacing the hydroxyl groups therein with different alkyl, aryl and other groups based on phosphorous acid. Phosphite plays an important role in improving the thermal stability of the tape, and its mechanism of action mainly includes the following aspects: First, antioxidant effect. Scavenging free radicals: During the thermal oxidation process of the tape, the oxidation reaction is usually a chain reaction, and the continuous generation and transfer of free radicals will accelerate the aging of the tape. Phosphites can interrupt the oxidation chain reaction by capturing free radicals, thereby slowing down the thermal oxidation rate of the tape. Synergistic antioxidant: Phosphites often work synergistically with hindered phenol antioxidants to improve the thermal stability of the tape. Hindered phenol antioxidants mainly terminate the chain reaction of free radicals by providing hydrogen atoms, while phosphites can react with peroxides to prevent them from further decomposing and producing free radicals, and can also reduce the oxidized hindered phenol antioxidants to restore their antioxidant activity. Reduce the oxidation reaction rate: Phosphites can also improve the thermal stability of the tape by reducing the rate of the oxidation reaction. Some studies have shown that the presence of phosphites can change the oxidation kinetics of polymers and slow down their oxidation reaction rates. The second is to enhance the stability of the molecular structure. Interaction with polymers: Phosphites can interact with polymer molecules in the tape to enhance the molecular structure stability of the polymer. This interaction may involve chemical bonding, hydrogen bonding or other physical interactions between phosphites and polymer molecules. Prevent molecular chain breakage: Under the action of heat, the polymer molecular chains in the tape are prone to breakage, resulting in a decrease in the performance of the tape. Phosphites can inhibit the breakage of molecular chains by interacting with polymer molecules, thereby improving the thermal stability of the tape.

[0031] Furthermore, the calcium stearate is a non-toxic, biocompatible organic salt. Calcium stearate has the following advantages when used as a raw material for preparing adhesive tape: First, it improves the surface quality. Calcium stearate can make the surface of the adhesive tape product smoother. It not only maintains the functions of an acidic scavenger and a lubricant, but also can improve the product quality in application and make up for the surface defects of the product. In the process of preparing the adhesive tape, calcium stearate can make the surface of the adhesive tape more flat and smooth, and improve the appearance quality of the adhesive tape. Second, it optimizes the processing performance. Calcium stearate has a good lubricating effect. In the production process of the adhesive tape, it can reduce the friction between the equipment and the adhesive tape, reduce the wear of the equipment, and improve the production efficiency. At the same time, by reducing the number of cleaning times caused by die blockage, the output of the adhesive tape can also be increased. Third, it enhances thermal stability. For some adhesive tapes that need to be used in a higher temperature environment, adding calcium stearate can improve their thermal stability, make the adhesive tape less prone to deformation, aging and other problems at higher temperatures, and extend the service life of the adhesive tape. Fourth, it is environmentally sustainable. In today's era of environmental protection, calcium stearate, as a relatively environmentally friendly material, has certain advantages.

[0032] Furthermore, acrylic glue, also known as acrylate adhesive, is a colorless polymer with natural viscosity and anti-oxidation. It is not easy to change color and lose viscosity during aging. Acrylic glue has the following advantages when used as a raw material for preparing tape: First, it has high stability. During the internal charging and discharging process of lithium-ion batteries, the tape selected from acrylic glue is very stable and basically does not react internally. Therefore, the tape prepared by it is not easy to produce adhesion when in contact with the cutting tool. Second, acrylic glue can better protect the internal structure of the battery and improve the performance and life of the battery.

[0033] Furthermore, the present invention uses polyethylene terephthalate and polyethylene resin together as the substrate of the lithium battery tape, which has the advantages of good mechanical properties, excellent electrical properties, chemical stability and processing performance, which are not possessed by other substrates. In the production and application of lithium batteries, the selection of a suitable tape substrate is crucial to improving the performance and safety of the battery. The present invention uses antioxidant 1076 as an antioxidant and phosphite as a thermal stabilizer. Compared with other antioxidants and thermal stabilizers, antioxidant 1076 and phosphite have good material compatibility with lithium battery tapes, can be evenly dispersed in the tape material, are more easily combined with the tape material, and will not delaminate or precipitate, thereby exerting the best antioxidant and thermal stabilization effect. The acrylic glue selected by the present invention has good stability, and the prepared tape is not easy to produce adhesion when in contact with a cutting tool. The present invention uses calcium stearate as a lubricant, which has the advantages of good thermal stability, strong compatibility, good anti-sticking property, low cost and good environmental protection, and plays an important role in improving processing performance, improving surface quality and preventing adhesion in the preparation of lithium battery tape. The tape of the present invention is not only resistant to high temperatures, but also has excellent adhesion and easy peeling properties, and is suitable for use as a lithium battery tape.

[0034] On the other hand, the present invention also provides a method for preparing an anti-sticking lithium battery high temperature resistant tape, comprising the following steps: (1) Drying: Dry the polyethylene terephthalate resin and polyethylene resin in a drying oven at 130-150°C for 3-5 hours to reduce the moisture content of the resin to less than 0.03%; (2) Mixing: Mix the dried resin with antioxidant 1076, phosphite and calcium stearate in a high-speed mixer. Set the mixer speed to 600-1000 rpm and the mixing time to 10-15 minutes; (3) Extrusion molding: Use a twin-screw extruder to add the mixed raw materials into the extruder hopper. Under the rotation of the screw, the raw materials are gradually plasticized and transported forward, and extruded through the slit die of the die head to form a thick sheet. The screw speed is set at 20-50 rpm according to the specifications and output requirements of the extruder; (4) Biaxial stretching: The extruded thick film is first stretched longitudinally. The stretching temperature is controlled at 85-95°C, the stretching ratio is 3-4 times, and the tension range is 8-12N / cm; the film after longitudinal stretching is then stretched transversely. The preheating temperature is 100-110°C, the stretching temperature is 110-120°C, and the stretching ratio is 3.5-4.5 times. The stretched film is heat-set in the setting area at a temperature of 200-220°C for 5-10 seconds; (5) Cooling: Cooling by cooling rollers, the temperature of which is controlled at 20-30°C, so that the film can be quickly cooled and shaped; (6) Corona treatment: Corona treatment is carried out by a corona treatment machine with a power of 2-5kW and a treatment time of 1-3 seconds; (7) Adhesive coating: Adhesive is coated on the surface of the substrate prepared in step 6 and dried.

[0035] Furthermore, the present invention provides a method for preparing an anti-sticking high temperature resistant tape for lithium batteries, which is obtained by drying, mixing, extrusion molding, biaxial stretching, cooling and corona treatment, and finally coating an adhesive. Biaxial stretching treatment can enhance tensile strength, improve puncture resistance and improve insulation performance, thereby improving the mechanical properties of the tape and optimizing electrical properties. Corona treatment can increase the viscosity of the tape, ensure that the tape can function stably under various environmental conditions, and enhance stability. The preparation method provided by the present invention effectively solves the problems of insufficient thermal stability, poor anti-sticking effect, and insufficient mechanical strength and adhesion of the tape in the prior art, and promotes the application and promotion of anti-sticking high temperature resistant tape for lithium batteries in the field of lithium battery manufacturing.

[0036] On the other hand, the present invention also provides an application of an anti-sticking knife lithium battery high temperature resistant tape, and the tape is applied in the lithium battery production process.

[0037] Examples The components in Examples 1-7 were configured according to Table 1 below.

[0038] Table 1 Content of each component in Examples 1-7

[0039] The method for preparing the above-mentioned adhesive tape comprises the following steps: (1) Drying: Dry the polyethylene terephthalate resin and polyethylene resin in a drying oven at 140°C for 5 hours to reduce the moisture content of the resin to less than 0.03%; (2) Mixing: Mix the dried resin with antioxidant 1076, phosphite and calcium stearate in a high-speed mixer. The mixer speed is set to 1000 rpm and the mixing time is 15 minutes. (3) Extrusion molding: Use a twin-screw extruder to add the mixed raw materials into the extruder hopper. Under the rotation of the screw, the raw materials are gradually plasticized and transported forward, and extruded through the slit die of the die head to form a thick sheet. The screw speed is set at 50 rpm according to the specifications and output requirements of the extruder; (4) Biaxial stretching: The extruded thick film is first stretched longitudinally. The stretching temperature is controlled at 95°C, the stretching ratio is 4 times, and the tension is 12N / cm; the film after longitudinal stretching is then stretched transversely. The preheating temperature is 110°C, the stretching temperature is 120°C, and the stretching ratio is 4.5 times. The stretched film is heat-set in the setting area at a temperature of 220°C for 10 seconds; (5) Cooling: Cooling by cooling rollers, the temperature of which is controlled at 30°C, so that the film is quickly cooled and shaped; (6) Corona treatment: Corona treatment is carried out by a corona treatment machine with a power of 5 kW and a treatment time of 3 seconds; (7) Apply adhesive on the surface of the substrate prepared in step 6 and dry it.

[0040] Comparative Example 1 The difference between Comparative Example 1 and Example 4 is that antioxidant 1076 is not added in Comparative Example 1.

[0041] Comparative Example 2 The difference between Comparative Example 2 and Example 4 is that no phosphite is added in Comparative Example 2.

[0042] Comparative Example 3 The difference between Comparative Example 3 and Example 4 is that no calcium stearate is added in Comparative Example 3.

[0043] Comparative Example 4 The difference between Comparative Example 4 and Example 4 is that the corona treatment in step 6 is not performed in the preparation of the adhesive tape in Comparative Example 4.

[0044] Test Example 1 This test example conducts a loop initial adhesion test on the tapes prepared in Examples 1-7 and Comparative Examples 1-4. The initial viscosity test is one of the important indicators for measuring the viscosity of the tape and can be used for product quality control and research. The loop initial adhesion is the separation force after the loop adhesive tape material (adhesive surface facing outward) is brought into contact with a standard test plate of a certain area at a certain speed. The loop adhesive tape is brought into contact with a test plate of a specified area under its own weight, and the force of the test tape is tested to pull it away from the test plate.

[0045] 1. Test Preparation 1. Test materials: sample ring: 24 mm wide, 175 mm circumference; stainless steel test plate: 1.5 mm-2.0 mm thick, 24 mm wide, 100 mm long; cleaning agent: one or more solvents selected from isopropyl alcohol, diacetone alcohol (4-hydroxy-4-methyl-2-pentanone), methanol, methyl ethyl ketone, acetone and n-heptanone; wiping material: medical gauze, cotton thread or cotton paper; the sample is the tape prepared in the examples and comparative examples; 2. Pretreatment: First, place the sample and test plate at a temperature of 23℃±1℃ and a relative humidity of 50%±5% for more than 24 hours; second, before testing, clean the stainless steel test plate with the above-mentioned cleaning agent and wiping material. After the test plate appears clean, repeat the cleaning three times to ensure that the cleaning agent is fully effective.

[0046] 2. Experimental steps 1. Install the stainless steel test plate in the lower fixture of the tensile testing machine and keep the test fixture level; 2. Bend the prepared tape sample into a teardrop-shaped ring sample ring with a circumference of 127mm and the adhesive side facing outward; fasten the two ends of the sample ring together with 24mm wide covering tape, and wrap the tail of the sample ring with the covering tape to prevent the adhesive from contaminating the clamp of the tensile testing machine; clamp the tail of the fastened sample ring in the upper clamp so that the bottom edge of the 24mm wide sample ring is level with the bottom edge of the upper clamp; 3. Turn on the chart recorder, start the tensile testing machine, and move the upper clamp downward at a speed of 300mm / min±10mm / min, so that the middle part of the sample ring is completely in contact with the central 24mm×24mm area of ​​the stainless steel test plate, and the edge hanging phenomenon cannot occur. When the upper clamp reaches the test position, the residence time is controlled within 3s, and the direction is immediately changed to move upward; 4. Record the maximum tensile force required for the specimen ring to detach from the stainless steel test plate.

[0047] 3. Test results The specific test results are shown in Table 2.

[0048] Table 2 Ring initial adhesion test results of different test samples

[0049] Combining the ring-shaped initial adhesion test results of the tapes prepared in Examples 1-7 and Comparative Examples 1-4, it can be seen that the viscosity of the tapes prepared in Examples 1-7 is better than that of Comparative Examples 1-4, indicating that the preparation method of the present application has good ring-shaped initial adhesion, thereby improving the quality of the tape.

[0050] Test Example 2 This test example tests the adhesiveness of the tapes prepared in Examples 1-7 and Comparative Examples 1-4. The adhesiveness of a tape refers to the persistence of the adhesiveness of the tape when a weight of a certain weight is vertically hung on the tape on the adhered object in the length direction. This is an important characteristic, an indicator for testing pressure-sensitive adhesives. If the adhesiveness is very poor, the tape will fall off easily and the purpose of bonding cannot be achieved. If the adhesiveness is too great, the adhered object will be easily damaged when it is separated from the adhered object. The adhesiveness of the adhesive tape can be selected according to different application scenarios and needs.

[0051] 1. Test Preparation 1. Test materials: Stainless steel test plate: thickness between 1.5-2.0mm, width of 40-50mm, length of 60-125mm; Pressing roller: Steel wheel covered with rubber, diameter (excluding rubber layer) about 84mm, width about 45mm, hardness of coated rubber is 80°±5°, thickness is about 6mm; Loading plate and weight: The material and size of the loading plate are the same as those of the test plate, and the total mass of the loading plate, weight and connecting pin is 1000g±10g; Cleaning agent: Applicable reagent grade or industrial grade or above solvent without residue, such as cyclohexane, gasoline, ethanol, isopropanol, toluene; Wiping material: Medical gauze, cotton thread or cotton paper; The sample is the tape prepared in the embodiment and comparative example; 2. Pretreatment: First, place the sample and test plate at a temperature of 23℃±2℃ and a relative humidity of 65%±5% for more than 24 hours; secondly, before the test, clean the stainless steel test plate and loading plate with the above-mentioned cleaning agent, and then wipe them carefully with a clean gauze. Repeat this cleaning for more than three times until the working surface of the plate is clean.

[0052] 2. Experimental steps 1. Paste the sample parallel to the longitudinal direction of the plate in the middle of the adjacent test plate and loading plate; 2. Use a roller to roll on the sample at a speed of about 300 mm / min. Note that when rolling, only the force generated by the mass of the roller can be applied to the sample; clamp the fixture at the free end of the sample, ensuring that the fixture clamps the entire width of the sample and that the load is evenly distributed; 3. Place the entire tape sample on the test stand, with the free end of the sample vertical, ensuring that no peeling force acts on the sample. Gently apply the weight to the fixture and record the time it takes for the sample to separate from the test plate.

[0053] 3. Test results The specific test results are shown in Table 3.

[0054] Table 3 Test results of adhesion of different test samples

[0055] Combining the adhesiveness test results of the tapes prepared in Examples 1-7 and Comparative Examples 1-4, it can be seen that the adhesiveness of the tapes prepared in Examples 1-7 is better than that of Comparative Examples 1-4, indicating that the preparation method of the present application has better adhesiveness, and further indicating that the tapes obtained in the present application have better quality.

[0056] Test Example 3 This test example tests the 180° peel force of the tapes prepared in Examples 1-7 and Comparative Examples 1-4. The 180° peel force test means that in the test, the bonded materials are gradually peeled off at an angle of 180° to evaluate the bonding strength of the materials in a completely sheared state. The principle is to stick the tape on the test board, then fix one end of the tape and peel off the other end at an angle of 180°. By measuring the force required during the peeling process, the adhesion performance of the tape can be evaluated, ensuring that the adhesion performance of the tape meets specific industrial standards and requirements, which is an important means of evaluating the quality of tape products.

[0057] 1. Test steps 1. Take a tape sample larger than 130mm, stick it on the surface of the mirror steel plate, roll it back and forth three times with a 2kg standard roller, and let it stand at room temperature for 20 minutes; 2. Fix the sample after standing still in the fixture of the tensile machine, set the experimental speed to 300mm / min, and perform a 180° peel force test; 3. Record the average peeling force of the smooth section during the peeling process.

[0058] 2. Test results The specific test results are shown in Table 4.

[0059] Table 4 180° peel force test results of different test samples

[0060] Combining the 180° peel force test results of the tapes prepared in Examples 1-7 and Comparative Examples 1-4, it can be seen that the adhesion of the tapes prepared in Examples 1-7 is better than that of Comparative Examples 1-4, indicating that the preparation method of the present application has good adhesion, and further indicating that the adhesion performance between the tapes obtained in the present application and the adherend is good.

[0061] Test Example 4 This test example tests the puncture resistance of the tapes prepared in Examples 1-7 and Comparative Examples 1-4. The puncture resistance of a tape refers to the ability of the tape to resist being pierced by sharp objects when subjected to a force perpendicular to its surface. This performance is a measure of the ability of the tape to protect its substrate or adhesive surface from penetration or damage when subjected to mechanical stress or impact. The testing principle is that a puncture cone pierces the tape sample at a certain rate in a direction perpendicular to the tape sample, and the maximum force required in the process is tested again. By testing the puncture resistance of the adhesive tape, it can be ensured that the product has sufficient strength and stability in different usage scenarios, thereby reducing the failure rate of the product during actual use.

[0062] 1. Test Preparation 1. Test materials: Test machine: a constant speed tensile test machine with a compressive function; a sample clamping device; a piercing device; the sample is the tape prepared in the embodiment and the comparative example; 2. Pretreatment: Place the tape sample, sample clamping device and piercing device at a temperature of 23±1℃ and a relative humidity of 50±5% for more than 24 hours.

[0063] 2. Experimental steps 1. Install the sample clamping device on the lower clamp of the constant rate tensile testing machine, and install the piercing device on the upper clamp of the constant rate tensile testing machine, so that the center of the piercing cone is aligned downward with the center of the circular hole of the sample clamping device; 2. Place the tape sample without tension or wrinkles, with the adhesive surface facing downward on the sample placement platform of the sample clamping device, cover it with the cover plate, and tighten the fixing screws to ensure that the sample does not slip horizontally during the test; 3. Turn on the constant speed tensile testing machine, select a needle with a diameter of 1mm, and set the puncture rate to 50mm / min; reset the force value before each test, start the puncture device to start the test, and the maximum force generated during the test is the puncture force; 4. Record the penetration force.

[0064] 3. Test results The specific test results are shown in Table 5.

[0065] Table 5 Test results of puncture resistance of different test samples

[0066] From the test results of the puncture resistance of the adhesive tapes prepared in Examples 1-7 and Comparative Examples 1-4, it can be seen that the puncture resistance of the adhesive tapes prepared in Examples 1-7 is better than that of Comparative Examples 1-4, indicating that the adhesive tapes obtained by the preparation method of the present application have the ability to protect their substrates or adhesive surfaces from penetration or damage when subjected to mechanical stress or impact.

[0067] Test Example 5 In this test example, the tapes prepared in Examples 1-7 and Comparative Examples 1-4 were subjected to breakdown voltage tests. The tape breakdown voltage test refers to the measurement of the voltage value corresponding to the voltage applied to the insulating tape under certain conditions until its insulation performance is destroyed, that is, electrical breakdown occurs. The basic principle of the tape breakdown voltage test is to use a high-voltage power supply to gradually increase the voltage applied to the test sample while monitoring the current changes of the sample. When the applied voltage exceeds the dielectric strength of the material, the electric field strength inside the material will reach or exceed its dielectric strength, causing electrical breakdown of the insulating material. The breakdown voltage is an important indicator to measure the insulation performance of the tape. If the breakdown voltage of the tape is too low, insulation failure is likely to occur during use, increasing safety risks. At the same time, by conducting a breakdown voltage test on the tape sample, potential quality problems can also be discovered to ensure that the product meets relevant standards and specifications and improve the safety and reliability of the product.

[0068] 1. Test steps 1. Use AC voltage, set the leakage current to 2mA, gradually increase the voltage from low to high, and read the maximum voltage load of the breakdown sample; 2. Record the experimental results.

[0069] 2. Test results The tape prepared in Examples 1-7 does not break down under the condition of 5.13KV AC, while the tape prepared in Comparative Examples 1-4 can break down under the condition of 5.13KV AC, indicating that the insulating performance of the tape prepared in Examples 1-7 is better than that of Comparative Examples 1-4. The tape obtained by the preparation method of the present application has good insulating performance, ensuring the safety of the product.

[0070] Test Example 6 This test example conducts electrolyte resistance test on the tapes prepared in Examples 1-7 and Comparative Examples 1-4. The electrolyte resistance test of the tape refers to the process of evaluating the ability of the tape to resist electrolyte erosion under specific conditions. The principle is to simulate the electrolyte environment that the tape may encounter in actual application, and evaluate the performance changes of the tape after contact with the electrolyte. Tapes with good electrolyte resistance can prevent leakage of the electrolyte, avoid internal short circuits and chemical corrosion of the battery, and thus improve the safety of the battery. At the same time, the electrolyte resistance of the tape directly affects the stability and service life of the battery. Good electrolyte resistance can ensure that the tape still maintains sufficient bonding performance after long-term contact with the electrolyte, preventing the battery performance from deteriorating.

[0071] 1. Test steps 1. Cut the tape sample into 25mm×50mm and stick it on the surface of 75μm aluminum foil material; 2. Use a 2.0 kg rubber roller to roll the sample back and forth twice, and then place the sample in a container containing electrolyte; 3. Place the container in an oven at 85°C for 4 hours; 4. Take out the container from the oven, cool it to room temperature, and observe whether the electrolyte changes color; whether the tape falls off the aluminum foil material; whether there is bulging between the adhesive layer and the aluminum foil material or whether it is penetrated by the electrolyte.

[0072] 2. Test results The results of observing whether the electrolyte changes color are as follows: After the tapes prepared in Examples 1-7 were soaked in the electrolyte, the electrolyte itself and the tapes maintained their original colors without any changes. This indicates that after the tapes prepared in the present invention were soaked in the electrolyte, no substances were released, and the performance of the electrolyte was not affected. After the tapes prepared in Comparative Examples 1-4 were soaked in the electrolyte, the electrolyte itself and the tapes changed in color, the electrolyte became turbid, and the tapes turned yellow, indicating that after the tapes prepared in the Comparative Examples were soaked in the electrolyte, substances were released, affecting the performance of the electrolyte.

[0073] The results of observing whether the tape fell off from the film material are as follows: the tapes prepared in Examples 1-7 did not fall off from the aluminum foil material, indicating that the tapes were still adhered to the aluminum foil surface. The tapes prepared in Comparative Examples 1-4 all fell off from the aluminum foil material, indicating that the tapes were not adhered to the aluminum foil surface.

[0074] In summary, the adhesive tape of the present invention has excellent resistance to lithium ion battery electrolyte.

[0075] Test Example 7 This test example tests the high temperature resistance of the tapes prepared in Examples 1-7 and Comparative Examples 1-4. The high temperature resistance test of the tape refers to the evaluation of the ability of the tape to maintain its physical and chemical properties unchanged in a high temperature environment. This method can be carried out by placing a dryer with an artificially prepared moisturizing solution in an oven, or directly using a constant temperature and humidity chamber. The high temperature resistance test can accurately determine whether the tape material is suitable for high temperature resistance, which is crucial to the safety and durability of the tape, especially the applicability and stability in a hot environment.

[0076] 1. Test Preparation 1. Test materials: moisturizing solution (using glycerol aqueous solution); the test samples are the tapes prepared in the examples and comparative examples; 2. Experimental steps 1. Place the dryer containing the moisturizing solution in an air circulation oven at a specified temperature (set to 65±2℃), and place the test samples horizontally on the perforated plate in the dryer. The test samples cannot touch each other. When the temperature in the oven reaches a balanced state, close the cover of the dryer. The test time is 7 days. 2. Observe and record the test results: If cracks, base material falling off or curling occurs, it is unqualified; if none of the above occurs, it is qualified.

[0077] 3. Test results The specific test results are shown in Table 6.

[0078] Table 6 High temperature resistance test results of different test samples

[0079] From the test results of high temperature resistance of the tapes prepared in Examples 1-7 and Comparative Examples 1-4, it can be seen that the high temperature resistance of the tapes prepared in Examples 1-7 is better than that of Comparative Examples 1-4, indicating that the tapes obtained by the preparation method of the present application have good applicability and stability in hot environments.

[0080] Test Example 8 This test example performs an anti-stick knife test on the tapes prepared in Examples 1-7 and Comparative Examples 1-4. The anti-stick knife test of the tape refers to the ability of the tape to prevent the blade from sticking during the cutting process. This test is usually used to determine whether the blade is easily adhered to the tape material during the production, processing or use of the tape, especially when cutting or punching operations are required, thereby affecting the processing efficiency and product quality. By testing the anti-stick knife performance of the tape, it is possible to select a suitable tape material, reduce the problem of blade sticking during the production process, improve processing efficiency, and ensure product quality.

[0081] 1. Test preparation: The test samples are the tapes prepared in the embodiments and comparative examples; 2. Experimental steps: Use a cutter to simulate the actual production and tape cutting during processing, and observe and record the sticking of the cutter.

[0082] 3. Test results The tapes prepared in Examples 1-7 have no traces of residual glue on the tool surface, while the tapes prepared in Comparative Examples 1-4 have slight traces of residual glue on the tool surface, indicating that the insulating performance of the tapes prepared in Examples 1-7 is better than that of Comparative Examples 1-4. The tapes obtained by the preparation method of the present application have good anti-stick knife performance, which can improve processing efficiency and ensure product quality.

[0083] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A high temperature resistant tape for lithium batteries with an anti-sticking knife, characterized in that: The adhesive tape comprises a substrate and an adhesive layer; The substrate comprises the following components, each component being calculated by weight: 75-87 parts of polyethylene terephthalate resin, 9-15 parts of polyethylene resin, 1-4 parts of antioxidant 1076, 2-3 parts of phosphite, and 1-3 parts of calcium stearate; The adhesive of the adhesive layer is acrylic glue; The substrate thickness is 20-25 μm; The thickness of the adhesive layer is 10-25 μm.

2. A method for preparing a high temperature resistant adhesive tape for anti-sticking lithium batteries as claimed in claim 1, characterized in that: The method comprises the following steps: 1) drying; 2) mixing; 3) extrusion molding; 4) biaxial stretching; 5) cooling; 6) corona treatment; and 7) coating adhesive.

3. The method for preparing a high temperature resistant adhesive tape for lithium batteries according to claim 2, characterized in that: The step 1) drying comprises: drying the polyethylene terephthalate resin and the polyethylene resin in a drying oven at 130-150° C. for 3-5 hours to make the moisture content of the resin less than 0.03%.

4. The method for preparing a high temperature resistant adhesive tape for anti-sticking lithium batteries according to claim 2, characterized in that: The step 2) mixing comprises: mixing the dried resin with antioxidant 1076, phosphite and calcium stearate in a high-speed mixer; the mixer speed is set to 600-1000 r / min, and the mixing time is 10-15 min.

5. The method for preparing a high temperature resistant adhesive tape for lithium batteries according to claim 2, characterized in that: The step 3) extrusion molding includes: using a twin-screw extruder, adding the mixed raw materials into the extruder hopper, under the rotation of the screw, the raw materials are gradually plasticized and conveyed forward, and extruded through the slit die of the die head to form a thick sheet; the screw speed is set at 20-50r / min according to the specifications and output requirements of the extruder.

6. The method for preparing a high temperature resistant adhesive tape for lithium batteries according to claim 2, characterized in that: The step 4) biaxial stretching comprises: firstly stretching the extruded thick sheet longitudinally; the stretching temperature is controlled at 85-95°C, the stretching ratio is 3-4 times, and the tension range is 8-12N / cm; the longitudinally stretched film is then stretched transversely; the preheating temperature is 100-110°C, the stretching temperature is 110-120°C, and the stretching ratio is 3.5-4.5 times; the stretched film is heat-set in a setting area at a temperature of 200-220°C for 5-10s.

7. The method for preparing a high temperature resistant adhesive tape for lithium batteries according to claim 2, characterized in that: The step 5) cooling includes: cooling by cooling rollers, wherein the temperature of the cooling rollers is controlled at 20-30° C., so that the film is quickly cooled and shaped.

8. The method for preparing a high temperature resistant adhesive tape for lithium batteries according to claim 2, characterized in that: The step 6) corona treatment comprises: performing corona treatment by a corona treatment machine with a power of 2-5 kW and a treatment time of 1-3 seconds.

9. The method for preparing a high temperature resistant adhesive tape for lithium batteries according to claim 2, characterized in that: The step 7) coating the adhesive comprises: coating the adhesive on the surface of the substrate prepared in step 6, and drying.

10. An application of the anti-sticking knife lithium battery high temperature resistant tape according to claim 1 or the anti-sticking knife lithium battery high temperature resistant tape prepared by the preparation method according to any one of claims 2 to 9, characterized in that: The adhesive tape is applied in the production process of lithium batteries.